Evaluation of rheological and mechanical properties of hot and warm mix asphalt mixtures containing Electric Arc Furnace Slag using gyratory compactor. (16th May 2023) - Ziaee, Seyed Ali; Moghadas Nejad, Fereidoon; Dareyni, Mohammad; Fakhri, Mansour
Highlights: Investigating workability and compactability due to the use of additives in HMA and WMA mixtures. Using indices to investigate the rheological properties of HMA and WMA mixtures. Investigating the type of gradation and properties of aggregates on the workability and compactability of HMA and WMA mixtures. Abstract: Workability and compactability are two key rheological properties of asphalt mixtures with direct impacts on pavement construction costs. These properties can be estimated by laboratory testing using the Superpave Gyratory Compactor (SGC). The compaction curves obtained from SGC can offer a general assessment of the workability, compactability, and even mechanical properties of asphalt mixtures. The most widely used workability and compactability indicators derived from these curves are the Workability Index (WI), Compaction Energy Index (CEI), Traffic Densification Index (TDI), and the slope of the semi-logarithmic compaction curve (k). In this study, these indicators were used to examine the workability, compactability, and mechanical properties of hot and warm mix asphalt (HMA and WMA) mixtures containing different amounts of Sasobit (0, 1.5, and 3%) and Electric Arc Furnace Slag or EAFS (0, 25, 50 and 75%) with two aggregate gradations (upper limit and middle range of Iran Highway Asphalt Paving Code No. 234). The results showed a decline in workability and compactability with the increase in EAFS content and also with the introduction of 1.5% Sasobit which was respectively caused by the high surface roughness of EAFS materials and the lack of sufficient workability by 1.5% sasobit at the mixing and compaction temperatures. However, the compactability of HMA mixtures with 3% Sasobit was comparable to that of HMA mixtures. Given the correlation between TDI and rutting resistance, experiential TDI values were used to develop a regression model for Flow Number (FN) estimation. The analysis of the variance of experimental results showed the significance of changes observed in the indicators. The study's findings demonstrated that, due to the high surface roughness of EAFS materials, the amount of additive and mixing and compaction temperatures should be chosen in accordance with the mixture's required workability and compactability. The TDI index can also be used to approximate the mechanical properties of asphalt mixtures during the initial stages of preparing laboratory specimens.